Sustainability Strategies of Indonesian Mega-Dairy Farm Business: A Case of Greenfields Indonesia - Adhitya Rahmana; Arief Daryanto; Siti Jahroh (School of Business, Bogor Agricultural University (SB-IPB), 2018)
The increase of milk import in Indonesia can be anticipated through the development of dairy farms based on mega-farm. Indonesia has already got dairy farms that adopt the mega-farm, one of which is the Greenfields Indonesia (GFI). GFI has become an export-oriented company, so GFI needs to pay attention to its sustainability on their business processes. This study was conducted at Dairy farm of Greenfields Indonesia. The purpose of this study was to analyze the business sustainability factors and to evaluate the factors of GFI dairy farming business based on the success factor of sustainability relation structure. The combination of delphi fuzzy and DEMATEL (Decision-Making Trial and Evaluation Laboratory) was used for data processing. The research results showed that the standardization of the company's management system was the first priority based on the relation structure. The priority could affect the resilience of farm models that depended on manure management impact and create animal care through the availability of management of feed and drinking water.Keywords: dairy farming, sustainable business development, fuzzy delphi method, dematel, management system